RI 6839 Influence Of Continuous Carbonization Method, Temperature, And Carrier Gas On The Amounts Of Individual Pyrolysis Products From A Sub-Bituminous Coal - Jr. Karr (The National Institute for Occupational Safety and Health (NIOSH), 1966)
The Bureau of Mines studied the influence of carbonization method, temperature, and carrier gas on the composition of eight different low-temperature tars produced from a Colorado subbituminous coal. A fluidized bed was compared with an entrained bed, temperature was varied from 500° C to 650° C, and external heating using recycle gas as the carrier gas was compared with internal heating using oxygen-containing gas. The entrained bed yielded significantly more m-cresol and m-ethylphenol, indicating that thermodynamic equilibrium was more nearly approached in the system. Increasing the temperature greatly increased the yield of benzenes and naphthalenes, while paraffins, olefins, and total tar acids were reduced. Using oxygen in the carrier gas decreased the yield of low-boiling phenols and increased that of paraffins and olefins at 650° C.